PEMBERDAYAAN PEMUDA BERBASIS POTENSI DIRI DI DESA MANUNGGAL JAYA - Mukhtar, Mukhtar; Zulkadrin, Zulkadrin (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2024)
The role of youth in village development is very important, both in terms of participation in program formulation/musyrembangdes, as well as control over policies. Manunggal Jaya Village, as a developed village, has not seen the participation of youth in its development. The most dominant factor behind this problem is human resources (youth) who do not yet understand their strategic role as youth and a low level of awareness and ability to empower them. The aim of this community service is to analyze the problems faced by youth, then determine the right strategy to overcome them. The strategies used include SWOT analysis and conducting education/training regarding leadership, managerial and strategies for influencing other people.